2018
DOI: 10.3892/ol.2018.8440
|View full text |Cite
|
Sign up to set email alerts
|

Miltirone‑induced apoptosis in cisplatin‑resistant lung cancer cells through upregulation of p53 signaling pathways

Abstract: The active ingredients of natural plants are important sources of antitumor agents. Miltirone is a major effective ingredient in traditional Chinese medicine and it is considered to have anti-infection and immunosuppressive activities. Clinically, it is often used for the treatment of arthritis and immune diseases. The effect of miltirone on cisplatin-resistant lung cancer cells has not been investigated to date. The present study aimed to examine the anticancer effect of miltirone in cisplatin-resistant lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Additionally, in vivo experimental HCC model revealed that treatment with miltirone significantly inhibited the HCC tumor growth. Our data concur with previous reports about the therapeutic potential of miltirone in cancer treatment 18 , 19 , 20 , 21 , 22 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Additionally, in vivo experimental HCC model revealed that treatment with miltirone significantly inhibited the HCC tumor growth. Our data concur with previous reports about the therapeutic potential of miltirone in cancer treatment 18 , 19 , 20 , 21 , 22 .…”
Section: Discussionsupporting
confidence: 93%
“…Apoptosis was generally considered as the predominant form of regulated cell death responsible for tumor therapies, a notion that was widely reported by numerous studies 40 , 41 . Miltirone used for cancer therapy attributed to its ability to inhibit cancer cell growth and to induce cancer cell apoptosis 19 , 20 , 21 . Zhou et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resistance of tumor cells to DDP allows cells to evade the cytotoxic effects of DDP, overcoming apoptosis (23); however, the underlying molecular mechanisms of DDP resistance require further investigation (24,25). miRNAs have been reported to be regulators of DDP resistance in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that compared with that of the control cells, the levels of S64 and S159 phosphorylation did not change significantly after the treatment with nicotine, while the phosphorylation of T163 was significantly enhanced. In the H1299 (Galluzzi et al, 2012;Zhu, 2018). The Mcl-1 protein is mainly localized to the mitochondrial outer membrane in the cells, but it has also been reported to be expressed in the nucleus.…”
Section: Nicotine Enhances the Viability Of H1299 Lung Cancer Cells By Enhancing The Phosphorylation Of The T163 Site Of Mcl-1mentioning
confidence: 99%